1991
DOI: 10.1063/1.460759
|View full text |Cite
|
Sign up to set email alerts
|

Energies of CH2OH, CH3O, and related compounds

Abstract: The Gaussian-2 (G2) theoretical procedure, based on ab initio molecular orbital theory, is used to calculate the energies of CH2OH, CH3O, and their cations. The resulting G2 adiabatic ionization potential for CH3O of 10.78 eV supports the new value of 10.726±0.008 eV reported by Ruscic and Berkowitz [J. Chem. Phys. 95, xxxx (1991)] from a photoionization study. A previous photoelectron result of 7.37±0.03 eV is probably an incorrect assignment. The G2 ionization potential for CH2OH is 7.45 eV, consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(55 citation statements)
references
References 21 publications
7
48
0
Order By: Relevance
“…[110] b Ref. [111] reduced by increasing the number of random walkers, N wlk , used in the MC evaluation of the HS integral in Eq. (5).…”
Section: 0166mentioning
confidence: 99%
“…[110] b Ref. [111] reduced by increasing the number of random walkers, N wlk , used in the MC evaluation of the HS integral in Eq. (5).…”
Section: 0166mentioning
confidence: 99%
“…The ground state surfaces of the hydrides are known 31 to contain another minimum corresponding to the isomeric species, CH 2 XH where X=O or S.…”
Section: 6mentioning
confidence: 99%
“…To assign the PES bands of BrOBr and HOBr, both G2 and OVGF calculations have been performed on the ground and ionic states corresponding to ionization of the electron of different molecular orbitals in the C 2v symmetry for BrOBr and in the Cs symmetry for HOBr. The G2 procedure has been described in detail by Curtiss et al 12 The OVGF calculations are shown in Ref. 13.…”
Section: Pes Measurementmentioning
confidence: 99%